2011
DOI: 10.1016/j.ijrobp.2010.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Role of Systemic Therapy in the Development of Lung Sequelae After Conformal Radiotherapy in Breast Cancer Patients

Abstract: Purpose: To analyze the risk of radiogenic lung damage in breast cancer patients after conformal radiotherapy and different forms of systemic treatment. Methods and Materials: In 328 patients receiving sequential taxane-based chemotherapy, concomitant hormone therapy (tamoxifen or aromatase inhibitors), or no adjuvant systemic therapy, symptomatic and asymptomatic lung sequelae were prospectively evaluated via the detection of visible CT abnormalities, 3 months or 1 year after the completion of the radiotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…The tolerance dose of RP is about 20 Gy; the more V 20Gy increases, the higher the incidence of RP [12,20-22]. …”
Section: Discussionmentioning
confidence: 99%
“…The tolerance dose of RP is about 20 Gy; the more V 20Gy increases, the higher the incidence of RP [12,20-22]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that radiation-induced lung sequelae affect as many as 9% of patients with breast cancer being treated with RT [24]. However, using computer-based radiation treatment planning systems dramatically decreased the incidence of these lung sequelae [25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies of conventional breast RT, the incidence of RLD was reported to be in the range of 37.0% to 100.0% by chest CT assessment [2,3,7,8,9]. Number of patients, target of RT (remnant breast vs. chest wall), fields of irradiation (local only vs. locoregional), and timing of follow-up chest CT were different in the studies.…”
Section: Discussionmentioning
confidence: 94%
“…Nonetheless, radiation can cause injury to organs surrounding breast, mainly to ipsilateral lung. Symptomatic or radiographic lung injury after conventional breast RT develops not infrequently with the incidence ranging between 5.5% and 100% according to previous reports [2,3,4,5,6,7,8,9]. …”
Section: Introductionmentioning
confidence: 98%